Denmark's comparative position regarding health status, healthcare provision, self-management and social support: Diabetes Attitudes, Wishes and Needs second study (DAWN2). Issue 2 (March 2015) - Hansen, Ulla Møller; Jones, Allan; Zander, Mette; Willaing, Ingrid
Aims: The aim of this study was to benchmark the Danish sample of the second Diabetes, Attitudes, Wishes and Needs (DAWN2) study with the global average in order to determine Denmark's comparative position for health status, healthcare provision, self-management and social support from the perspective of people with diabetes, family members of people with diabetes and healthcare professionals. Methods: A total of 502 Danish people with diabetes (PWD), 122 adult family members of people with diabetes (FM) and 283 healthcare professionals (HCPs) participated in the study. Data on healthcare provision and physical and psychosocial wellbeing were collected from the 17 participating countries. Results: Psychological wellbeing was higher among Danish PWD; conversely, self-management behaviour of PWD ranked below the global average. A substantial gap was found in the perceptions of PWD and HCPs regarding the extent to which healthcare provision was deemed person-centred. The gap was found to be larger, however, when looking at the global data. Danish FM reported higher education participation and satisfaction rates as well as lower distress than the global average, but there appears to be an untapped potential when it comes to converting education participation of FM into social support for PWD. Conclusions: Our findings suggest that PWD in Denmark rank above the global average on measures of psychological wellbeing, despite psychological wellbeing being under-prioritised by HCP. However, there is room for improvement when it comes to self-management behaviours. Special attention is needed to address this issue without compromising the psychological wellbeing of the PWD.